2014
DOI: 10.1063/1.4867013
|View full text |Cite
|
Sign up to set email alerts
|

Large piezoelectric coefficient and ferroelectric nanodomain switching in Ba(Ti0.80Zr0.20)O3-0.5(Ba0.70Ca0.30)TiO3 nanofibers and thin films

Abstract: Large piezoelectric coefficient and ferroelectric nanodomain switching in Ba(Ti0.80Zr0.20)O3-0.5(Ba0.70Ca 0.30)TiO3 nanofibers and thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Piorra reported the piezoelectric response of approximately 80 pm/V and a dielectric coefficient of about ε r = 1010 for 0.5BZT–0.5BCT thin film deposited by pulsed laser deposition, these obtained values are close to PZT thin film . Very recently, Jalalian showed that large piezoelectric coefficient in 0.5BZT–0.5BCT thin films can reach up to 140 pm/V, which is higher than that of PZT thin films. Therefore, 0.5BZT–0.5BCT thin film is found to be a potential candidate to replace PZT in MEMS devices.…”
Section: Introductionmentioning
confidence: 87%
“…Piorra reported the piezoelectric response of approximately 80 pm/V and a dielectric coefficient of about ε r = 1010 for 0.5BZT–0.5BCT thin film deposited by pulsed laser deposition, these obtained values are close to PZT thin film . Very recently, Jalalian showed that large piezoelectric coefficient in 0.5BZT–0.5BCT thin films can reach up to 140 pm/V, which is higher than that of PZT thin films. Therefore, 0.5BZT–0.5BCT thin film is found to be a potential candidate to replace PZT in MEMS devices.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, a significant breakthrough has been made in (1− x )Ba(Zr 0.2 Ti 0.8 )O 3 – x (Ba 0.7 Ca 0.3 )TiO 3 , which exhibits surprisingly high piezoelectric coefficient arising from a morphotropic phase boundary (MPB) at x = 0.5 (BCZT) starting from a cubic‐rhombohedral‐tetragonal triple point . In contrast to numerous research on BCZT ceramics, the systematical studies on the growth and characterization of BCZT thin films still remain at an infancy stage, though these thin films are expected to provide a variety range of applications such as energy harvesting, high‐frequency medical ultrasound imaging and microfluidic control, etc . The lack of progress in BCZT thin films can be primarily attributed to the challenges associated with growth of high‐quality thin films.…”
Section: Introductionmentioning
confidence: 99%
“…4 In contrast to numerous research on BCZT ceramics, the systematical studies on the growth and characterization of BCZT thin films still remain at an infancy stage, though these thin films are expected to provide a variety range of applications such as energy harvesting, high-frequency medical ultrasound imaging and microfluidic control, etc. [5][6][7] The lack of progress in BCZT thin films can be primarily attributed to the challenges associated with growth of high-quality thin films. Although BCZT thin films have been heavily studied over the past years, the reported physical properties of the films were very scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [330] reported a reversible electric-field-induced strain of over 5% in BiFeO 3 films. More recently, very large piezoelectricity in lead-free nanostructures sintered as thin films and nanofibers have been reported by Jalalian et al [331]. Additionally, some polymeric nanostructured ferroelectric-related materials such as PVDF nanowires also have been reported to have enhanced piezoelectric properties with outstanding piezoelectric effect [332], which is promising in practical applications.…”
Section: Important Phenomena In Ferroelectric Thin Filmsmentioning
confidence: 99%